An Incidental Finding of a Double-Lumen Trachea - Piersiala, Krzysztof (2021)
The aim of this case report is to present an incidental finding of a firm tracheal septum in a 61-year-old woman. The patient was admitted to the hospital with mild dyspnea and a preliminary diagnosis of a tracheal subglottic stenosis. During microlaryngoscopy, just below the subglottic stenosis, a firm, vertical symphysis (septum), forming a double-lumen trachea was found. There was no record of any previous difficulties with intubation. A computed tomography scan performed after the microlaryngoscopy revealed an airway branch arising from the trachea at the level of thyroid gland and joining its lumen below. The radiological and endoscopic findings in the presented case hardly resemble the conditions described in the literature, as the discovered septum does not have a pseudomembranous nature, nor does it form a tracheal bronchus. Therefore, the finding is thought to be an unusual complication of multiple intubations in the past. This is an extremely rare finding and it is important to share our experience in managing a patient with the aforementioned post-intubation complications.